ChildTalks+: a study protocol of a pre-post controlled, paired design study on the use of preventive intervention for children of parents with a mental illness with focus on eating disorders - Farářová, Adéla; Papežová, Hana; Gricová, Jana; Štěpánková, Tereza; Čapek, Václav; Reedtz, Charlotte; Lauritzen, Camilla; van Doesum, Karin (BMC psychiatry, 2022)
BACKGROUND: Children of parents with a mental illness are at high risk of developing a mental disorder as a result of transgenerational transmission. Without effective intervention, they could form the next generation of psychiatric patients. ChildTalks+ is a preventive intervention involving four structured psychoeducational sessions designed for parents affected by a mental disorder and their children. Its aim is to reduce the risk of mental disorders in children of parents with mental illness. This study draws on our clinical practice and involves a group of patients with eating disorders. The aim of the project, which will run in the Czech Republic, is to evaluate the effectiveness of ChildTalks+ methodology. METHODS: ChildTalks+ therapists (professionals from health, social, and educational facilities) will recruit 66 families where a parent is treated for a mental disorder and the family includes children aged 6-18. Paired allocation into an intervention group (N = 33) and a control group (N = 33) will be based on the number of risk factors identified in the family. Both groups will complete questionnaires at the baseline, post-test, and follow-up assessments after six and 12 months. The intervention group will receive the ChildTalks+ intervention within 2 months of the baseline assessment; the control group after the last assessment. Questionnaires will be completed by parents and children aged 12+ and, in two cases, 15+ years. Quantitative data will be supplemented with qualitative data from ChildTalks+ therapists working with patients with eating disorders. DISCUSSION: The ChildTalks+ intervention is expected to strengthen parenting competencies and family protective factors, improve family communication, increase awareness of parental mental health issues, and improve the wellbeing of children of parents with mental illness with long-term sustainable outcomes. The study should contribute to the evidence base for the ChildTalks+ program and help identify key themes in the implementation of similar preventive interventions. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT05554458. Registered 26 September 2022. Retrospectively registered.
Keywords: Controlled Clinical Trials as Topic; klinické zkoušky kontrolované jako téma; Parents; poruchy příjmu potravy; Child; rodičovství; lidé; průzkumy a dotazníky; Feeding and Eating Disorders; Research Design; dítě; Surveys and Questionnaires; Parenting; výzkumný projekt; rodiče; Humans